2019
DOI: 10.3847/2041-8213/ab5c1e
|View full text |Cite
|
Sign up to set email alerts
|

Filling the Mass Gap: How Kilonova Observations Can Unveil the Nature of the Compact Object Merging with the Neutron Star

Abstract: In this letter we focus on the peculiar case of a coalescing compact-object binary whose chirp mass is compatible both with a neutron star-neutron star and black hole-neutron star system, with the black hole in the ∼ 3 − 5 M range defined as the mass gap". Some models of core-collapse supernovae predict the formation of such low-mass black holes and a recent observation seems to confirm their existence. Here we show that the nature of the companion to the neutron star can be inferred from the properties of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…The best limiting magnitudes correspond to absolute magnitudes −16 mag for both events, with typical observations ranging from M∼ −16.5 mag to M∼ −17.5 mag. AT2017gfo 12 , the optical counterpart to GW170817, peaked at M∼ −16 mag, and KNe from NSBH models are typically brighter than those from BNSs [13][14][15] , indicating that our observations are in the magnitude range required for detection.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The best limiting magnitudes correspond to absolute magnitudes −16 mag for both events, with typical observations ranging from M∼ −16.5 mag to M∼ −17.5 mag. AT2017gfo 12 , the optical counterpart to GW170817, peaked at M∼ −16 mag, and KNe from NSBH models are typically brighter than those from BNSs [13][14][15] , indicating that our observations are in the magnitude range required for detection.…”
mentioning
confidence: 87%
“…Several works in the literature [13][14][15] have shown that KNe from NSBH mergers are generally brighter than those resulting from BNS mergers. A similar behaviour is found in NSBH and BNS models computed here and in Ref.…”
mentioning
confidence: 99%
“…The predictions for the inferred ejecta mass, average velocity, and electron fraction differs for NSBH mergers and BNS mergers. Delineation between the progenitors and remnants will have to rely on combinations of ejecta mass, velocities, kilonova color, and multimessenger determination of inclination (Barbieri et al 2019(Barbieri et al , 2020. A self-consistent picture with GW-determined masses SGRB and kilonova observations will strengthen such claims.…”
Section: Progenitor Classification and The Existence Of Neutron Star-mentioning
confidence: 98%
“…If this heavy component is a low-mass black hole, it challenges existence of the mass gap between black holes and neutron stars (Kreidberg et al 2012;Özel et al 2012). Thus, the determination of the binary type is essential to obtain robust astrophysical knowledge (see Barbieri et al 2019, for related work in this direction).…”
Section: Introductionmentioning
confidence: 99%